A living customary law of commercial contracting in South Africa: some law-related hypotheses. Issue 3 (2nd September 2017) - Hutchison, Andrew; Sibanda, Nkanyiso
Abstract: Inspired by calls to 'decolonise' South African law and legal education, this paper will posit some hypotheses as to the nature of a living customary law of commercial contracting from the perspectives of two South African contract law teachers. An account of the commercial format of customary contracting is largely absent from the law reports and leading legal textbooks in this country. The dominant narrative in existing legal sources, however, (which may be stereotyped), is of African communalism prevailing in customary contract practice. This is reflected, for example, in the discourse on 'ubuntu', which is being used at present as a vehicle for the constitutional transformation of the South African common law of contract. Other existing empirical accounts from discourses such as economics and anthropology also suggest, however, that contracting in indigenous African communities rests on notions of trust and community. This is reinforced by the existence of informal township dispute resolution structures. We will thus posit a central hypothesis that customary commercial contracting is relational in nature, using an inter-disciplinary literature review and drawing on the lived experiences of the authors. Other related hypotheses will also be developed. Ultimate truth here is a matter for future empirical study.